RADIO SPECTRA OF COMPLETE SAMPLE OF GALACTIC SUPERNOVA REMNANT - Trushkin, S. A. (Одеські астрономічні публікації, 2017)
We present radio continuum spectra for 192 Galactic supernova remnants (SNRs) from 220 known and included in Green's (1998) catalog. These spectra include most of measurements available in literature, as well as multi- frequency measurements of nearly 120 SNRs with the RATAN-600 radio telescope. The measurements have been placed on the same absolute flux density scale of Baars (1977). The presented compilation has given a possibility of plotting quite accurate spectra accounting for the thermal plasma free-free absorption in fitting the spectra accounted for. From 190 spectra seventy eight (41%) have clear frequency turnover caused, apparently, by absorption in the thermal foreground within Milky Way. Frequencies of (ντ=1) are distributed from 5 to 365 MHz, with medium value: 32 MHz. There are no correlations between Galactic coordinates, spectral index and ντ=1 in the sample of SNRs, but there is significant correlation of the frequency ντ=1 and distances, estimated from Σ - D relation.